2009
DOI: 10.1017/s0021859609990402
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between yield, growth and spike weight in wheat under phosphorus deficiency and shading

Abstract: SU MMARYThe effect of phosphorus deficiency on yield formation in spring wheat (Triticum aestivum cv. Prointa Oasis) was investigated, focusing on crop growth and dry matter partitioning during the spike growth period (SGP), which is critical for grain number determination. Two experiments combining shading and P deficiency were performed at Balcarce, Argentina (37x45kS). The main treatments were two levels of soil P-availability : low P, a naturally low P fertility soil (7 . 0 and 5 . 5 mg Bray extractable P/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 34 publications
(103 reference statements)
4
18
0
Order By: Relevance
“…However, according to the genotype × P rate interaction in Experiment 1, RUE was decreased by P deficiency in six genotypes, where yield reduction was on average 53% (in contrast to the 33% in Experiment 2). This is in line with the RUE reduction reported in other crops, where yield reduction was greater than 40% under P deficiency (Plénet et al, 2000;Rodríguez et al, 2000;Lázaro et al, 2010). Therefore, RUE reductions in potato in response to P deficiency could be expected when P availability is so deficient for growth that causes high yield reductions.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, according to the genotype × P rate interaction in Experiment 1, RUE was decreased by P deficiency in six genotypes, where yield reduction was on average 53% (in contrast to the 33% in Experiment 2). This is in line with the RUE reduction reported in other crops, where yield reduction was greater than 40% under P deficiency (Plénet et al, 2000;Rodríguez et al, 2000;Lázaro et al, 2010). Therefore, RUE reductions in potato in response to P deficiency could be expected when P availability is so deficient for growth that causes high yield reductions.…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, there is much less information about how the RUE of potato responds to P availability. Leaf photosynthesis rates of other species have been shown to decrease with P deficiency (Plesnicar et al, 1994;Halsted and Lynch, 1996;Rodríguez et al, 1998a,b); however, contrasting results have been found regarding RUE responses to P deficiency (Plénet et al, 2000;Rodríguez et al, 2000;Fletcher et al, 2008b;Lázaro et al, 2010;Sandaña and Pinochet, 2011;Sandaña et al, 2012). In the study of Jenkins and Ali (1999), the RUE of potato crops was not affected by the P supply.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies have shown that P has a profound effect on plant growth and development, with increased P fertilization often increasing the grain yield of oilseed crops (Gao et al, 2006;Grant et al, 2010). Some of these observations of P effects on oilseed crops are similar to those found in other crops, such as spring wheat (Triticum aestivum L.; Lázaro et al, 2010) and soybean (Glycine max; Lauer and Blevins, 1989). Some of these observations of P effects on oilseed crops are similar to those found in other crops, such as spring wheat (Triticum aestivum L.; Lázaro et al, 2010) and soybean (Glycine max; Lauer and Blevins, 1989).…”
Section: Optimizing Phosphorus Fertilization Promotes Dry Matter Accumentioning
confidence: 77%
“…The Pi uptake rates are higher between pH 5.0 and 6.0 where HPO À2 4 dominates (Furihata, Suzuki, & Sakurai, 1992;Ullrich Eberius, Novacky, & Van Bel, 1984). P deficiency affects the growth and yield in several crop plants including rice (Oryza sativa) (Wissuwa & Ae, 2001a), maize (Zea mays) (Plenet, Etchebest, Mollier, & Pellerin, 2000), wheat (Triticum aestivum) (Lazaro, Abbate, Cogliatti, & Andrade, 2010), sorghum (Sorghum bicolor) (Camacho, Malavolta, Guerrero Alves, & Camacho, 2002), common bean (Phaseolus vulgaris) (Bonser, Lynch, & Snapp, 1996), soybean (Glycine max) (Mahamood, Abayomi, & Aduloju, 2009) and foxtail millet (Setaria italica) (Ceasar et al, 2014). About 5.7 billion hectares of agricultural land around the world lack Pi (Batjes, 1997; Heuer et al, 2009).…”
mentioning
confidence: 99%